EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA PADA PEMERINTAH DESA DI KOTA BATU - Shenia Nilla Sari; M Faisal Abdullah (Program Studi Ekonomi Pembangunan, 2019)
The purpose of this research is to find out the effectiveness of the management of village fund allocation in the Village Government in Batu City and to find out the opportunities and challenges faced in managing ADD. Data analysis used in this study is to use the effectiveness measurement ratio in accordance with the effectiveness criteria and use the SWOT analysis. The results of this study indicate the effectiveness of the management of village fund allocations in 19 villages in Batu City in 2017-2018 already in effective criteria. Opportunities faced in ADD management are the role of the role of the city government, the sub-district government and village facilitators, the synergy between the city and village governments, the information system, the increasing welfare of the community and the economy and improving village infrastructure facilities and infrastructure. The challenges faced in the management of ADD are the uncertainty of the ADD disbursement process, the reduced budget from the city government, the success rate of the program that is not according to plan and the delay in regulation regarding village financial management.Keywords : ADD, Effectiveness village funds allocation, SWOT analysis